Relationship between Blood Glucose, Cholesterol and Blood Pressure in Diabetes Mellitus Patients with Diabetic Ulcers: Hubungan Glukosa Darah, Kolesterol Dengan Tekanan Darah Pada Pasien Diabetes Melitus Dengan Ulkus Diabetikum - Siti Khosnaini; Puspitasari (Academia Open, 2021)
Diabetes mellitus is a chronic disease caused by heredity or environment. According to Riskesdas, 2018 states that based on a doctor's diagnosis, the number of diabetes mellitus cases in Indonesia has increased to 2% compared to the results of Rikesdas in 2013 which was only 1.5%. The purpose of this study was to determine the relationship between blood glucose, cholesterol and blood pressure in diabetes mellitus patients with diabetic ulcers. The research design used was cross sectional. The research sample was 30 patients with diabetes mellitus with diabetic ulcers at Wonoayu Luka House. This research was conducted from February to March 2021. The results showed that there was no relationship between blood glucose and cholesterol with blood pressure (r=0.043, r=-0.199) after the Pearson correlation test was performed.